Love rules : silent Hollywood and the rise of the managerial class - Cooper, Mark Garrett (University of Minnesota Press, 2003)
Through close study of such films as Birth of a Nation, Enoch Arden, The Crowd, Why Change Your Wife? and The Jazz Singer, Mark Garrett Cooper uncovers an intimate connection between Hollywood romances of the silent era and the empowerment of a managerial class.
Keywords: Love in motion pictures.; Silent films -- United States -- History and criticism.; Motion picture audiences.; Race relations in motion pictures.; Amour au cinéma.; Films muets -- États-Unis -- Histoire et critique.; Cinéma -- Publics.; Relations raciales au cinéma.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Love in motion pictures; Motion picture audiences; Race relations in motion pictures; Silent films; United States; Electronic book.; Criticism, interpretation, etc.